Effect of oral administration of a continuous 18 day regimen of meloxicam on ovulation: experience of a randomized controlled trial - Jesam, C.; Salvatierra, A.M.; Schwartz, J.L.; Fuentes, A.; Croxatto, H.B. (Contraception (Stoneham), 2014)
Cyclooxygenase-2 (COX-2) is expressed in all female reproductive organs. Therefore, inhibitors of COX-2 may affect reproductive function. We evaluated the effect of extended administration of meloxicam on ovulation and the menstrual cycle. Our hypothesis was that meloxicam administered from menstrual cycle day 5- 22 could interfere with follicular rupture, without disrupting the menstrual cycle, and could be a potential non-hormonal contraceptive method. The study was conducted in 56 healthy sterilized women. Before the onset of treatment and after the end of treatment, participants were observed during a control cycle to ensure that they had progesterone (P4) serum levels (>12 nmol/l) consistent with ovulation. Participants were treated for 18 days, during three consecutive cycles. They were randomized to 15 or 30 mg/day. The menstrual cycle was monitored with serial ultrasound and hormone assays in blood. Fifty-six volunteers completed the study. In 55% of cycles treated with 15 mg/day and in 78% of cycles treated with 30mg/day (p<0.001) we observed dysfunctional ovulation defined as follicular rupture not preceded 24–48 h earlier by an LH peak or preceded by a blunted LH peak (<21 IU/l) or not followed by an elevated serum P4 level >12 nmol/l. Ovulation was observed in 44.6% and in 21.7% of women in the lower dose group and the higher dose group, respectively. There were no differences between the two doses in other parameters measured. There were no serious adverse events and adverse events were not different between doses or between control and treated cycles. Although administration of meloxicam on menstrual cycle days 5- 22 resulted in a dose-dependent inhibition of ovulation, more than 20% of subjects had normal ovulation with the highest dose. Previous studies have shown that oral meloxicam can delay follicle rupture. This study investigated daily oral meloxicam as a non-hormonal contraceptive. Since ovulation occurs in over 20% of cycles even with a high dose of 30 mg daily, it is not likely that the approach would be a highly effective contraceptive strategy.